WeChat use and cross-cultural adaptation of international students in China : The mediating role of social self-efficacy - Kai, Zhang; Ting, Su Hie (Journal of Intercultural Communication (JICC), 2024)
An increasing number of international students are pursuing studies in China and encounter challenges and uncertainty in a new foreign environment. Cross-cultural adaptation is influenced by social self-efficacy, social interaction, and WeChat use but little is known about the interaction of these three factors in influencing cross-cultural adaptation. The study examined the mediating role of social self-efficacy in the relationship between WeChat use and cross-cultural adaptation for international students in China. Method: Questionnaire data were collected from 215 international students in four universities in China. A majority were from Asian countries and aged 18-25. The students had high levels of WeChat use and cross-cultural adaptation, and a moderately high level of social self-efficacy. Pearson’s correlation test results revealed that WeChat use was a positive predictor of social self-efficacy and cross-cultural adaptation. Similarly, social self-efficacy was a positive predictor of cross-cultural adaptation. Linear regression analyses showed that the association between WeChat use and cross-cultural adaptation was partially mediated by social self-efficacy. The findings suggest that social self-efficacy has the potential to act as a protective factor in the cross-cultural adaptation of international students in China because, in the event of low WeChat use, the students may still be better able to adapt to cross-cultural environments if they have high social self-efficacy.